Buddhist Ethics: A Philosophical Exploration - Garfield, Jay L. (Buddhist Philosophy for Philosophers Ser., 2021)
Buddhist Ethics presents an outline of Buddhist ethical thought. It is not a defense of Buddhist approaches to ethics as opposed to any other, nor is it a critique of the Western tradition. Garfield presents a broad overview of a range of Buddhist approaches to the question of moral philosophy. He argues that while there are important points of contact with these Western frameworks, Buddhist ethics is distinctive, and is a kind of moral phenomenology that is concerned with the ways in which we experience ourselves as agents and others as moral fellows.